The Concept of Al-Jumhuriyah Wa Al-Ahkam in Political Philosophy of Ibn Rushd - Siraj , Fuad Mahbub; Nor, Mohd Roslan Mohd (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
In political conversation, Ibn Rushd named his political philosophy as “Al-Jumhuriyah wa al-Ahkam” (Republic and Law). This political thought is a form of integration of science and deed. This study employs a literature and historical approach to analyze Ibn Rushd's political philosophy, focusing on his integration of religion and reason in shaping political principles. In this political context, Ibn Rushd prioritizes freedom and independence. In Ibn Rushd’s perspective, independence is not without rules, but independence and freedom should be compatible with religion. Likewise, in Ibn Rushd’s perspective, such freedom and independence is a reflection of democracy. In politics, Ibn Rushd’s thinking is similar to the thoughts of previous philosophers who reconcile religion and philosophy. The findings highlight that Ibn Rushd’s philosophy emphasizes the harmony between religion and rationality as essential to upholding democratic values in governance. There is no contradiction between reason and religion, according to Ibn Rushd, and therefore it is important for reason and religion to work together to uphold the principles of democracy in a country. This study contributes to the scholarly discourse by providing a methodological framework that bridges classical Islamic philosophy with contemporary political theory, offering insights into how Ibn Rushd’s ideas can inform modern governance.